2007
DOI: 10.7861/clinmedicine.7-5-457
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of a glossary aid patient understanding of the letters sent to their general practitioner?

Abstract: -The NHS Plan suggests that all patients should be offered copies of letters regarding their treatment which are currently sent from a specialist clinic to their general practitioner (GP). Previous work has suggested that this enhances patient satisfaction, but medical letters can be difficult to understand. This report concerns the production and evaluation of a lung disease glossary to enhance patient understanding of terms used within the letter sent to their GP. Non-clinical staff reviewed 219 letters sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…There are undoubtedly other possible formats, as well as educational aides (for example, videos), that could be used to promote patient comprehension that are not discussed here. With the increased use of EMR and online portals, there are even greater possibilities for improvement, such as enhancing interface design to include links to additional information (for example, glossary, other websites) to promote comprehension and usability [ 17 , 127 – 129 ]. Using an online system for reviewing results may also present the opportunity to create interactive reports that will further engage the patient and potentially promote increased understanding and recall.…”
Section: Moving Towards a Patient-friendly Test Reporting Formatmentioning
confidence: 99%
“…There are undoubtedly other possible formats, as well as educational aides (for example, videos), that could be used to promote patient comprehension that are not discussed here. With the increased use of EMR and online portals, there are even greater possibilities for improvement, such as enhancing interface design to include links to additional information (for example, glossary, other websites) to promote comprehension and usability [ 17 , 127 – 129 ]. Using an online system for reviewing results may also present the opportunity to create interactive reports that will further engage the patient and potentially promote increased understanding and recall.…”
Section: Moving Towards a Patient-friendly Test Reporting Formatmentioning
confidence: 99%
“…However little work has been done to identify the impact of health literacy on compliance in COPD or its effect upon what patients do or do not do in a consultation. We have previously shown how patients do not fully understand the medical letters they receive (Roberts and Partridge 2006) and have tried to provide further information to patients to improve their understanding (Brown et al 2007). However, there is little published evidence regarding the modifying of consultations/guidelines for patients with COPD who might have cognitive problems or limited health literacy.…”
Section: Adherence With Copd Therapymentioning
confidence: 99%
“…However, patients often do not fully understand the medical terms detailed within the letters they receive and the letters to primary care physicians copied to patients have been shown to be quite diffi cult for patients to read (Roberts and Partridge 2006). We designed a respiratory glossary which can be used as a tool in aiding respiratory patients understanding of the letter being sent to their GP (Brown et al 2007). It is important that the magnitude of low health literacy in the population is recognized and instead of trying to identify these vulnerable patient groups, other methods should be used to reinforce the comprehensibility for all patients especially those with longterm conditions.…”
Section: Consultations With Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients often do not fully understand the terminology within the letters they receive and letters to the referring doctor have been shown to be quite difficult for patients to read [61]. We have designed a respiratory glossary ( figure 3) and shown that this seems to be a useful tool in aiding respiratory patients' understanding of letters sent to their GP [62].…”
Section: During the Consultationmentioning
confidence: 99%